Satellite Technology for Internet of Things: An Overview - Adiprabowo, Tjahjo; Ramdani, Dani; Daud, Pamungkas; Andriana, Andriana; Zulkarnain, Zulkarnain; Nasrullah, Nanang; Vertus, Olly; Rahman, Sutisna Abdul; Simarmata, Melissa T. A. (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2025)
This article is about satellite review which is essential for internet connectivity and also the development of IoT and other applications, this article contains history, performance, challenges, and research opportunities in the field of satellite development. Satellite development can be applied to improving the performance of various applications such as IoT, Education, and Medical, as well as real-time monitoring such as monitoring pets such as horses and cows in large numbers, as well as other essential applications such as the medical world. Satellite development is essential for applications in the world today and in the future. Satellite technology development is tailored to the needs, for example with the Mini Cube Satellite used for the development of LPWAN IoT technology orbiting in Low Earth Orbit (LEO).